2020
DOI: 10.3390/plants9080996
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Validation of Reference Genes for Quantitative Real-Time PCR in White Clover (Trifolium repens L.) Involved in Five Abiotic Stresses

Abstract: White clover (Trifolium repens L.) is a widely cultivated cool-season perennial forage legume in temperate grassland systems. Many studies have analyzed the gene expression in this grass species using quantitative real-time reverse transcription PCR (qRT-PCR). The selection of stable reference genes for qRT-PCR is crucial. However, there was no detailed study on reference genes in different tissues of white clover under various abiotic stress conditions. Herein, 14 candidate reference genes (ACT7, ACT101, TUA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Ideally, the stability of the reference gene should not be influenced by the experimental conditions. Nevertheless, several studies point out that the mRNA transcript levels could be affected by tissue type [ 19 , 20 ], developmental stage [ 26 ], treatment type [ 27 , 28 ], and genotype [ 26 ] as well. Furthermore, the expression stability of the same reference gene may also depend on the investigated species [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, the stability of the reference gene should not be influenced by the experimental conditions. Nevertheless, several studies point out that the mRNA transcript levels could be affected by tissue type [ 19 , 20 ], developmental stage [ 26 ], treatment type [ 27 , 28 ], and genotype [ 26 ] as well. Furthermore, the expression stability of the same reference gene may also depend on the investigated species [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of candidate reference genes were chosen based on existing literature that utilised them as suitable stable internal control genes for qRT-PCR analysis in different plant species [ 18 , 21 , 28 , 41 ]. The applicability of ADPR (Unigene cluster: Ta30797) and PGD (Unigene cluster: Ta2291) (candidate reference genes proposed by Paolacci et al [ 27 ]) were confirmed previously by our research group in wheat ( Triticum aestivum L.) under different stress conditions [ 40 , 42 , 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ideally, the stability of the reference gene should not be in uenced by the experimental conditions. Nevertheless, several studies point out, that the mRNA transcript levels could be affected by tissue type [11,12], developmental stage [18] treatment type [19,20] and genotype [18] as well. Furthermore, the expression stability of the same reference gene may also depend on the investigated species [21].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of candidate reference genes were chosen based on their description being stable internal control genes for qRT-PCR analysis in different plant species ( [10,13,19,34]. The applicability of ADPR (Unigene cluster: Ta30797) and PGD (Unigene cluster: Ta2291) (candidate reference genes proposed by [20]) were con rmed previously by our research group in wheat (Triticum aestivum L.) under different stress conditions [33,[35][36][37].…”
Section: Reference Gene Selection and Pcr Primer Designmentioning
confidence: 99%
“…For accurate normalization purpose, the expression of reference genes should have minimal variation independent of tissue types, developmental stages, and experimental treatments (Wong and Medrano, 2005;Huang et al, 2016Huang et al, , 2019. Indeed, such ideal universal reference genes do not exist at all (Cubero-Leon et al, 2012;Pu et al, 2020). Therefore, it is crucial to select and validate reliable reference genes for target gene expressions under specific experimental conditions in the species studied.…”
Section: Transcriptional Responses Under Ammonia Challenge and Implications Of Ammonia Stress Coping Strategiesmentioning
confidence: 99%